A3_5 1.21 Jigawatts!?! - Flood, Laura; Holland, Katie; Leversha, Thomas; Manley, Max (Physics Special Topics, 2022)
In this paper we are investigating how much power it would take for the DeLorean from Back to the Future to reach the 88mph speed required to travel in time. We calculated that when the DeLorean is flying it requires less power than when it is driving on a road to reach the target velocity, and in both cases it requires far less power than the 1.21GW that the flux capacitor can provide.